P03.13 Age-induced changes in anti-tumor immunity alter the tumor immune infiltrate and reduce response to immune-oncology treatments. (1st October 2020) - Sitnikova, S; Morrow, M; Valge-Archer, V; Wilkinson, RW; Robinson, MJ; Dovedi, SJ
Abstract : Background: Immuno-Oncology research relies heavily on murine syngeneic tumor models. However, whilst the median age for a cancer diagnosis is 65 years or older, for practical purposes the majority of preclinical studies are conducted in young mice, despite the fact that ageing has been shown to have a significant impact on the immune response. Materials and Methods: Using aged mice bearing CT26 tumors, we analysed how aging impacts the immune composition of the tumor, spleen and tumor-draining lymph nodes by flow cytometry. Results: We found many age-related changes between aged (60–72 weeks old) and young (6–8 weeks old) mice, such as a reduction in the naïve T cell population and a decreased CD8/Treg ratio in aged animals. Profiling of co-inhibitory and co-stimulatory receptor expression levels on immune cells in aged versus young mice also identified altered expression profiles in both the periphery and tumor. We hypothesised that these differences may contribute to impaired anti-cancer immune responses in aged mice. To investigate this, we compared the anti-tumor efficacy of immune checkpoint blockade (PD-L1 and CTLA-4) and T-cell costimulation (OX-40) in aged versus young mice. Our data demonstrate that aged mice retained their capacity to generate effective anti-tumor immune responses, albeit often attenuated when compared to the responses observed in young mice. Conclusions: These differences highlight the potential importance of age-related immunological changes in assessing and refining the translational insights gained from preclinical mouse models. Disclosure Information: S. Sitnikova: A. Employment (full or part-time); Significant; AstraZeneca. M. Morrow: A. Employment (full or part-time); Significant; AstraZeneca. V. Valge-Archer: A. Employment (full or part-time); Significant; AstraZeneca. R.W. Wilkinson: A. Employment (full or part-time); Significant; AstraZeneca. M.J. Robinson: A. Employment (full or part-time); Significant; AstraZeneca. S.J. Dovedi: A. Employment (full or part-time); Significant; AstraZeneca.